Edukasi Prosedur Anestesi Spinal Dengan Audio Visual Pada Pasien Sectio Caesarea di Rsud Dr Soedirman Kebumen - Sarumpaet, Pitri; Suryani, Roro Lintang; Burhan, Asmat (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Sectio Caesarea is a procedure used to make an incision in the mother’s uterine wall. In this procedure , surgery and anesthesia are stressful because there is a risk to the integrity of a person’s body and soul because they do not know the actions to be taken. Purpose : Based on this PkM, it is to provide education on spinal anesthesia procedures with audiovisuals is section caesarea’s patients. Methode : The future community service method provides knowledge about education on spinal anesthesia procedures with audiovisuals in section caesarea patients. After being given education about spinal anesthesia, it is hoped that patients will be able to understand the spinal anesthesia procedure. The target of this PkM is pregnant women who will undergo childbirth through the section caesarea technique at RSUD dr. Soedirman Kebumen. Results : The results of this activity show the level of knowledge in patients in the pre-test in the sufficient category with a score of 4-5 and in the post-test it is categorized as good with a score of 6-7. Output : The output of the activity used in the form of audiovisual videos and publication articles which are expected to be able to add knowledge to patients and can be used as learning maerials at Harapan Bangsa University, Purwokerto. The results of this activity can be published in the Dikti Scientific Journal.